VARIABILIDAD DE LA RESPUESTA SECRETORA GASTRICA A LA HISTAMINA INFLUENCIA DE LA COLERA - FIGUEROA, C G (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
The commercial value of the shrimp industry in the Gulf of California is discussed Summaries are given of the catch wt and value in the states of Nayarit, Sinaloa and Sonora for each year from 1940 to 1944
BOL INST ESTUD MED BIOL
Keywords: VARIABILIDAD, RESPUESTA, GASTRICA, INFLUENCIA , COLERA; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA